2017
DOI: 10.1016/j.wneu.2017.08.170
|View full text |Cite
|
Sign up to set email alerts
|

Why Does the Health-Related Quality of Life in Idiopathic Normal-Pressure Hydrocephalus Fail to Improve Despite the Favorable Clinical Outcome?

Abstract: Frail patients suffering from certain pre-existing comorbidities may not experience improvement in generic HRQoL despite of a favorable clinical disease-specific response. Acknowledging the comorbidity burden of the patient may help clinicians and the patients to understand the conflict between patient-reported and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While the gait performance is, by far, the most objective measure for outcome assessment in iNPH, other outcome indicators should accompany it. Performance in activities of daily living and patient reported outcome measures might enhance clinical evaluation in this regard [10, 33], but should not be used alone [33]. Unfortunately, we do not have follow-up information regarding the 14 probable or possible iNPH patients that were not shunted (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the gait performance is, by far, the most objective measure for outcome assessment in iNPH, other outcome indicators should accompany it. Performance in activities of daily living and patient reported outcome measures might enhance clinical evaluation in this regard [10, 33], but should not be used alone [33]. Unfortunately, we do not have follow-up information regarding the 14 probable or possible iNPH patients that were not shunted (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Junkkari et al [ 37 ] showed that 43% of 145 iNPH patients experienced a clinically significant improvement in HRQoL one year after shunt surgery. In the same material, the authors found that participants with a poor starting point (a higher degree of iNPH symptoms) were less likely to experience improved HRQoL despite a favourable clinical outcome [ 38 ]. iNPH patients who had to wait for surgery had a worse clinical outcome compared to those who were operated on early [ 30 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of co morbid AD to INPH on the short and long term shunt surgery outcome had been studied. There are encouraging studies showing that gait speed, gait quality, psychomotor speed, attention, overall cognitive function, urination improved in patients with INPH after shunt surgery irrespective of the presence of AD pathology [15][16][17].…”
Section: Introductionmentioning
confidence: 99%